FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN NIAT MAHASISWA KOS UNTUK BERPERILAKU HIDUP BERSIH DAN SEHAT DI TEMBALANG SEMARANG - Gehapsa, Muhammad Saifuddin (Jurnal Kesehatan Masyarakat (Undip), 2016)
Health Behavior, especially The clean and healthy living is important factor affected degrees health of a person or society.based on the 2014 at Rowosari  Public Health Center, the lowest percentage households practicing clean and healty life behavior is in urban village tembalang is as much as 82 %. This study aims to analyze factors that deals with intention students boarding to behave clean and healthy living. This study used Observasional with Cross Sectional Survey approach.The population of this research is Tembalang Village community with 5.485 people and sample research are 99 respondents. The samples were collected by using Accidental Sampling Technique. This Study was conducted in Juni-Juli 2015 at Village Tembalang Semarang.Sources of research data using primary data and secondary data. This research use univariate and bivariate.The result  were analysed by using Chi Square. The result of this study revealed that boarding students intention to clean and healty life behavior were correlated to Behavioral Belief and Evaluational Belief. Boarding student intention to clean and healty life behavior were not correlated to Normative Belief and Motivation to Comply.